Trends and Thematic Evolution in Digital Policy Research: A Bibliometric Analysis - Fridayani, Helen Dian; Younus, Muhammad; Isnadi, Yuli; Nurmandi, Achmad; Widyasari, Sindy (Journal Public Policy, 2025)
This study presents a bibliometric analysis of digital policy research, evaluating its thematic evolution and theoretical underpinnings across international journals. Utilizing the Scopus search engine, the research identifies and classifies digital policy publications from 2013 to 2023, and VOSviewer software was employed to visualize trends, network linkages, and information production. The findings indicate a notable lack of theory-driven research in the digital policy domain, with a majority of studies focusing on empirical or applied aspects rather than foundational theory. This gap is particularly pronounced in areas like cybersecurity, data privacy, and digital governance. Additionally, the study reveals that interdisciplinary journals contribute more to theory-based digital policy research than specialized publications. The research calls for greater integration of theoretical frameworks in digital policy studies to address global digital challenges better. It highlights the need for scholars to explicitly link their work to theory, thus enriching policy development and offering more comprehensive solutions to emerging technological issues. Failure to incorporate theory consistently represents a missed opportunity to influence the broader discourse on digital governance and policy making.